Platypnoea and orthodeoxia in the hepatopulmonary syndrome. Issue 11 (26th November 2019) - Surridge, Anna; Atkinson, Jane; Aujayeb, Avinash
Abstract : A 71-year-old female patient with alcohol-induced cirrhosis presented with symptoms of dyspnoea. Previous extensive investigations had detected no apparent cause. Platypnoea and orthodeoxia were observed. A bubble echocardiogram revealed significant intracardiac shunting and a diagnosis of hepatopulmonary syndrome was made. The patient was discharged on home oxygen and referred for liver transplantation.